Account of the Excavation of the Roman Station at Inchtuthil, Perthshire, undertaken by the Society of Antiquaries of Scotland in 1901: (II) Description of the Plans - Ross, Thomas (Proceedings of the Society of Antiquaries of Scotland, 1902)